Perbandingan Metode SAW, WP Dan Topsis Dalam Penentuan Pembiayaan: (Studi Kasus BMT El-Raushan) - Dede Supiyan (Jurnal Ilmiah Informatika, 2019)
Decision support system is the composition of a computer-based information system that functions as a supporter of decision making in an organization or company. Decision making in determining the provision of financing is very important because with the right decision the provision of financing can run well. Decision making method is useful for determining the best alternative from a number of other alternatives based on certain criteria, including the simple additive weighting method, Weighted Product and Technique For Order Preference by Similarity to Ideal Solution. A comparison of the methods of this decision support system is carried out to determine which method provides the highest accuracy value of the financing data for the El-Raushan BMT cooperative. Based on comparison of the SAW Method, Weighted Product and TOPSIS methods show that the Weighted Product method is more accurate than the simple additive weighting method Technique For Order Preference by Similarity to Ideal Solution. Judging from the value of the accuracy of the three methods with the highest accuracy WP (Weighted Product) method with an accuracy value of 94%.